IMPACT OF CORPORATE IAMGE ON THE USE OF BANK SERVICE: A CASE OF CONVENTIONAL vs. ISLAMIC BANKS MARKETING - Bhatti, Ishaq M.; Awan, Hayat Muhammad; Siddiquei, Ahmed Nabeel (Annales Universitatis Apulensis Series Oeconomica, 2017)
ABSTRACT: This paper compares Bank's corporate image on customer’s satisfaction to enhance marketability between Islamic (IB) and conventional banks (CB) in Pakistan. A sample of 320 customers is selected from four major cities of the country to ask about brand image, firm's reputation, ethics and corporate social responsibility (CSR). It is observed that the word-of-mouth, firm's reputation and security are the main drivers for CB's whereas for the IB's, the brand familiarity, reputation, CSR and bank's communication and Shariah compliancy. Quantitative methodology is used to analyze the collected data. It is proposed that the management of these banks should make efforts to implement these findings to enhance both types of banking services in the country to best satisfaction of their clients.